PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KOMISI PEMILIHAN UMUM (KPU) DI KABUPATEN - Siti Zahara (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2023)
This study aims to explain the effect of motivation and work discipline on employee performance. This type of research is quantitative research with the unit of analysis at the General Election Commission in Musi Banyuasin Regency, with a total population of 30 respondents. Sampling was done by non-probability sampling method, simple saturated technique, where all members of the population were used as samples. The analysis technique in this research is descriptive statistics and inferential statistics with a structural equation modeling (SEM) approach using lisrel software. The results of this study indicate that motivation has a positive and significant effect on employee performance. While work discipline has no effect on employee performance. The influence of motivation and work discipline simultaneously motivation and work discipline has a significant effect on performance and contributes 61.1%. So the higher the motivation and work discipline simultaneously, the better the performance of the Musi Banyuasin General Election Commission employees.